Handbook of educational psychology and students with special needs - Martin, Andrew J., 1966-; Sperling, Rayne A.; Newton, Kristie Jones, 1973- (Educational psychology handbook series., 2020)
"Handbook of Educational Psychology and Students with Special Needs provides educational and psychological stakeholders with critical domain-specific expertise on the factors and processes relevant to learning for students with special needs. This includes students with attention-deficit/hyperactivity disorder, other executive function difficulties, behavior and emotional disorders, autism spectrum disorder, intellectual disabilities, learning disabilities, dyslexia, language and communication difficulties, physical and sensory disabilities, and more. With the bulk of educational psychology focused on "mainstream" or "typically developing" learners, relatively little educational psychology theory, research, measurement, and practice has attended to students with "special needs." The factors and processes studied within this discipline-motivation, emotions, cognitive load, school environments, and more-are relevant to all learners, including those at risk or disabled. Integrating guidance from the DSM-5 by the American Psychiatric Association and the International Classification of Diseases (ICD-10) by the World Health Organization, this book synthesizes and builds on existing interdisciplinary research to establish a broad case for effective psycho-educational theory, research, and practice that addresses learners with special needs. Twenty-seven chapters by experts in the field are structured into three sections on diverse special needs categories, perspectives from major educational psychology theories, and constructs relevant to special needs learning, development, and knowledge building"--